What Do Physician Assistant Students Know About Nutrition? A Survey of Attitudes, Self-Perceived Proficiency, and Knowledge During Three Stages of Physician Assistant Education. Issue 3 (September 2016) - Favia, Megan; Moore, Amy; Kelly, Patrick; Werner, Christine
Abstract : Purpose: This study applied a cross-sectional design and analyzed the nutrition knowledge and attitudes of physician assistant (PA) students during 3 stages of PA education. Methods: The PA students from the class of 2014, 2015, and 2016 attending a midwestern university were surveyed using Qualtrics. Descriptive statistics and analysis of variance tests were performed to determine the difference between the 3 cohorts on "previous nutrition knowledge, " "attitudes, " and "knowledge" subscores and total scores. A post hoc analysis was performed to determine the differences between groups. Results: A statistically significant difference was found in the mean total score between classes, with the class of 2014 scoring 17 points higher on average than the class of 2016. Conclusion: These results suggest that positive nutrition attitudes and knowledge among PA students from this sample were lacking. This study suggests a possible need for revision of nutrition education provided by PA programs.